Improvement of Engineering Properties of Peat with Palm Oil Clinker - Rahman, Muhammad; Leblouba, M.; Pakrashi, V. (University Putra Malaysia Press, 2014)
The aim of this study is to investigate the effects of Palm Oil Clinker (POC) added as a stabilizer forimproving the strength of peat. Cement and POC are added into peat up to 50% of the maximum dry unitweight. Treated peat achieved higher dry unit weight, almost 2.5 times as compared to untreated peat.Unconfined compressive strength (UCS) of treated peat is also investigated for soaked and unsoakedconditions. The results show that curing time improved the unconfined compressive strength of treatedsample and increased by a factor of 20 and 11 for unsoaked and soaked conditions after 28 days ofcuring, respectively. The treated samples added with POC can be related to an increase in unconfinedcompressive strength for long time curing.